A Web-Based Information System for Supervising Students’ Final Projects and Scientific Papers - Dr. drg. Supriyana , M.Pd.; Bambang Sutomo; Setya Wijayanta; Esti Handayani; Sri Wahyuni; Waris Agung Widodo (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2026)
Conventional final-project supervision in higher education is often ineffective, poorly documented, and difficult to monitor in real time. This study aimed to develop SIBIMA, a web-based information system for final-project supervision that supports communication, documentation, and monitoring of student supervision activities. This research used a Research and Development approach with the Waterfall model, consisting of needs analysis, system design, implementation, and testing. Functional testing was conducted using black-box testing, while the user interface and user experience were evaluated by 62 respondents, including program administrators, supervisors, and heads of study programs. The developed system facilitated title submission, supervision, revision documentation, scheduling, and structured monitoring of final-project progress. The evaluation indicated that the system functioned as intended and was well received by users across the main supervision workflows. SIBIMA has strong potential as a digital solution for improving the effectiveness of communication, supervision documentation, and monitoring of final-project preparation.